Peliosanthes purpureiflora (Asparagaceae), a new species from China - Meng, Kai Kai; Qu, Jun Ru; Li, Ren Kun; Lu, Li Yan; Meng, Tao; Wang, Li Ping; Feng, Hui Zhe (Phytotaxa, 2025)
A new species, Peliosanthes purpureiflora, endemic to South China, has been described. The new species exhibits several distinguishing characters including the terete pedicel, perianth segments spreading in the same plane, the truncate-conical corona with a 6-subdentate distal margin, the smaller ovary with a noticeable gap between the corona, and a longer style, approximately 1.2 mm in length, with three wing-like projections.